Strategi Penanganan Anak Tidak Sekolah (ATS) di Kota Pekalongan - Puji Astuti, Tri (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
At the beginning of 2024, Pekalongan City received ATS data from Dapodik Kemendikbudristek RI as many as 1,739 ATS Graduated and didn’t continue school / Dropped Out. Efforts to handle ATS have been carried out since 2021, especially in 2024, Pekalongan City will become one of the locus for replicating good practices for handling ATS organized by the Central Java Provincial Government in collaboration with UNICEF Representatives for Java and Bali. This research aims to determine the strategies that need to be carried out by the Pekalongan City Government in handling ATS in Pekalongan City in order to obtain optimal results. Using quantitative or qualitative data from primary and secondary data, research was carried out using SWOT analysis (Strengths, Weaknesses, Opportunities and Threats), namely identifying and evaluating internal and external factors that support or do not support the handling of ATS in Pekalongan City. From the results of data collection (field verification) as of August 31 2024, it was found that the 5 (five) most activities of ATS were as workers (53.52%), no routine activities (38.30%), playing with Hand-Phones (3.56%), taking care of families (1.89%), and street children (1.14%). Based on causal aspects, social aspects are the most dominant aspect (33.46%), followed by culture (23.39%), economy (20.67%), and services (3.10%). From the research results, it was found that handling ATS needs to receive attention and support from all participants because handling ATS is not the responsibility of one Regional Apparatus but rather multi-stakeholders including the government, educational institutions, non-governmental organizations and the community. The strategy for handling ATS is carried out through: Strengthening and developing regional policies and regulations, Strengthening and developing institutions or organizations, Strengthening data collection and application development, Increasing access and quality of equal education services, and Strengthening literacy and capacity of communities and aparatus.